Data for Does historical land use affect the regional distribution of fleshy-fruited woody plants? (Arnell et al, 2019) - Matilda Arnell (Stockholm University, 2019)
This is the dataset for the article "Does historical land use affect the regional distribution of fleshy-fruited woody plants?" by M. Arnell, S.A.O. Cousins and O. Eriksson. The dataset contains a readme file and a csv file with data. Please consult the readme for information regarding data structure, and the journal article for sampling information and scientific context.
Keywords: 50104 Landscape Ecology; Ecology; Ekologi